Peranan Masyarakat Dalam Membina Moral Peserta Didik SMAN I Siberut Selatan Kecamatan Siberut Selatan Kabupaten Kepulauan Mentawai - -, Marinus - (Pendidikan Geografi, 2014)
This study aimed to obtain information, analyze and describe data on the role of society in fostering moral learners SMAN I South District of South Siberut Siberut Mentawai Islands as seen from: 1 teachers role in fostering moral learners, 2 The role of parents in fostering moral learners, 3 the role of the head of customs in fostering moral learners. This study uses qualitative research is the subject of this study were taken by purposive sampling. Data collected by using interviews, observation, and documentation. In analyzing the data, obtained from interviews, observation, and documentation, the data analysis techniques used in this study was a qualitative analysis techniques with the following lines: data reduction, data display, and conclusion. The results showed that the role of society in fostering moral learners SMAN I South District of South Siberut Siberut Mentawai Islands can be explained that: (1) The role of teachers in fostering moral learners can be disclosed that still need to increase the role of the teacher in terms of guidance and religious values should many provide role models for learners to create moral behavior better. (2) The role of parents in fostering moral learners can be disclosed that still need to increase the role of the parents in terms of giving learners control of the association and have a lot to teach religious values to students to enhance the moral development better. (3) The role of the head of customs in fostering moral learners can be disclosed that still need improvement in teaching norms prevailing in the society.